OsGF14b positively regulates panicle blast resistance, but negatively regulates leaf blast resistance in rice - Liu, Qing; Yang, Jianyuan; Zhang, Shaohong; Zhao, Junliang; Feng, Aiqing; Yang, Tifeng; Wang, Xiaofei; Mao, Xinxue; Dong, Jingfang; Zhu, Xiaoyuan; Leung, Hei; Leach, Jan E.; et al. (Scientific Societies, 2016)
Although 14-3-3 proteins have been reported to be involved in responses to biotic stresses in plants, their functions in rice blast, the most destructive disease in rice, are largely unknown. Only GF14e has been confirmed to negatively regulate leaf blast. We report that GF14b is highly expressed in seedlings and panicles during blast infection. Rice plants overexpressing GF14b show enhanced resistance to panicle blast but are susceptible to leaf blast. In contrast, GF14b-silenced plants show increased susceptibility to panicle blast but enhanced resistance to leaf blast. Yeast one-hybrid assays demonstrate that WRKY71 binds to the promoter of GF14b and modulates its expression. Overexpression of GF14b induces expression of jasmonic acid (JA) synthesis-related genes but suppresses expression of salicylic acid (SA) synthesis-related genes. In contrast, suppressed GF14b expression causes decreased expression of JA synthesis-related genes but activation of SA synthesis-related genes. These results suggest that GF14b positively regulates panicle blast resistance but negatively regulates leaf blast resistance, and that GF14b-mediated disease resistance is associated with the JA- and SA-dependent pathway. The different functions for 14-3-3 proteins in leaf and panicle blast provide new evidence that leaf and panicle blast resistance are controlled by different mechanisms.